(Nw)QækNQNSXKIJ àARRÆN^A(B. (NsERÆQ LISTÆWOK DO ROKOWINI WTRATI LEGENDARNOGO UKRAÇNSXKOGO FUTBOLÆSTA dMITRA bÆLOUSA (B/s)E - (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s; (NwASKAN(B, (Nw(B. (Nw(B.s ((NwASILX wASILXOWI^(B)s; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2022)
(Nu WIDAWNICTW)QÆ (B"(NrODOWÆD(B" (NWIJ[LA U SWÆT SERÆQ LISTÆWOK (B"(NwækNQNSXKIJ àARRÆN^A(B" (NPRISWQ^ENA ROKOWINAM WTRATI LEGENDARNOGO UKRAÇNSXKOGO FUTBOLÆSTA dMITRA bÆLOUSA(B, (NWIHÆDCQ Z SELA wÆKNO (B((NzASTAWNÆWSXKOGO(B, (NNINÆ ~ERNÆWECXKOGO RAJONU(B). (NbUKOWINSXKÆ POETI wASILX dVURAN TA wASILX wASKAN POETI^NIM SLOWOM ZGADU@TX LEGENDARNOGO FUTBOLÆSTA(B. (NtAKOV PRO RÆDKÆSNE OBDAROWANNQ Æ FUTBOLXNE BEZSMERTQ UKRAÇNSXKOÇ (B"(NZÆRKI(B" (NW LISTÆWKAH WMÆ]ENO (B40 (NSPONUKALXNO(B-(NOPOWÆDALXNIH PE^ALEJ FUTBOLÆSTÆW(B, (NQKÆ WISTUPALI ^I WISTUPA@TX ZA TÆ ^I ÆN[Æ KOLEKTIWI(B.s)E
(NsPEC)QÆALXNIJ PROÃKT ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nACÆONALXNOÇ SPÆLKI PISXMENNIKÆW uKRAÇNI Æ wÆKNQNSXKOÇ tgs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E